The optimists : a novel - Platzer, Brian (Little Brown and Company, 2026)
"Mr. Keating is an extraordinary teacher: brilliant, dedicated, and possibly a few pages ahead in a book no one else is reading. He's a magician, able to enchant fourteen-year-olds into a love of writing and literature. Yet no student has lived up to the promise of their potential more than Clara Hightower. Over the course of three decades, Clara goes from kindergarten thief to a high school genius, Silicon Valley celebrity, and, finally, animal rights activist turned terrorist. But to tell Clara's story, Mr. Keating must tell his own, including his courtship and marriage, his dreams of writing and comedy, his days in the classroom in lower Manhattan and his rivalry and friendship with his head of school, and his eventual stroke and the isolation that follows."--